2010
DOI: 10.1111/j.1365-2567.2010.03277.x
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T cells against human papillomavirus‐18 E7 in patients with high‐grade cervical lesions associate with the absence of the virus in the cervix

Abstract: IntroductionCervical cancer is the second most common cancer in women worldwide and is associated with human papillomavirus (HPV) persistent infection. [1][2][3] In fact, HPV is detected in > 99% of cervical cancer and is now considered the primary aetiological agent in cervical cancer tumorigenesis.4 Development of HPV-related neoplastic lesions, from cervical intraepithelial neoplasia (CIN) to cervical carcinoma, is the result of infection by high-risk HPV, during which integration of the viral episome into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…In this regard, the presence of tumour-infiltrating lymphocytes, specific for HPV 16 in the majority of HPV-positive SCCs of the head and neck, provides evidence in favour of a specific T cell reaction to HPV antigens in HPV type 16 associated SCC [34]. In addition, high numbers of HPV-specific T cells in peripheral blood have been described in several studies of head and neck SCC [35,36], vulvar intraepithelial neoplasia [37] and cervical intraepithelial neoplasia lesions [38][39][40]. Functional data showed that HPV-specific T cells are able to mount a response against HPV-positive cancer cells [35,41].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In this regard, the presence of tumour-infiltrating lymphocytes, specific for HPV 16 in the majority of HPV-positive SCCs of the head and neck, provides evidence in favour of a specific T cell reaction to HPV antigens in HPV type 16 associated SCC [34]. In addition, high numbers of HPV-specific T cells in peripheral blood have been described in several studies of head and neck SCC [35,36], vulvar intraepithelial neoplasia [37] and cervical intraepithelial neoplasia lesions [38][39][40]. Functional data showed that HPV-specific T cells are able to mount a response against HPV-positive cancer cells [35,41].…”
Section: Discussionmentioning
confidence: 93%
“…The LCD-array HPV 3.5C uses primer pairs and capture probes specific for HPV types 06, 11, 16, 18, 31, 33, 35, 39, 42, 44, 45, Tumours negative for HPV were examined a second time using a multiplex HPV genotyping assay. GP5+/GP6+ primer-based multiplex PCR and genotyping were performed using Luminex-based multiplexed genotyping (MPG, multiplexed HPV genotyping, Multimetrix, Heidelberg, Germany) for detection of 18 high-risk HPV genotypes (HPV 16,18,26,31,33,35,39,45,51, 52, 53, 56, 58, 59, 66, 68, 73 and 82) and 6 low-risk HPV genotypes (HPV 6, 11, 42, 43, 44 and 70) [13,14] Quantification of lymphocytes The number of labelled lymphocytes was counted for each case in five different representative high-power fields (HPFs) (×40 objective; 22-mm field of view ocular) of tumour tissue and adjacent stroma using an Olympus BX40 microscope (Olympus Europe Holding GmbH, Hamburg, Germany), blinded to the HPV status of tumours.…”
Section: Immunohistologymentioning
confidence: 99%
“…The expansion of HPV16-specific CD4+ T cell was found in all nine patients tested in detail, and in three patients, also HPV16-specific CD8+ T cells were detected. The bias toward CD4+ T cell reactivity against HPV-derived epitopes is not likely a result of the culture method used here, but more a reflection of what is generally found in the spontaneous T cell response to HPV in cervical cancer [17, 18, 2931], as well as among TILs from patients with head and neck cancer [32]. The T helper type 1 (Th1) cytokine IFNγ was produced in all LNMC cultures and in some cases also the Th2 cytokines IL-10 and IL-5.…”
Section: Discussionmentioning
confidence: 99%
“…The virus infects basal epithelial cells through microabrasions on the epithelial surface. The oncogenesis depends on the integration of the viral episome into the DNA of the epithelial cell [ 300 ] and on the activity of the viral oncoproteins E6 and E7 [ 301 ]. Both CD4 + and CD8 + T-cells are capable of recognizing these proteins.…”
Section: Immunity Of Female Genital Mucosa Hiv/aids and Stdsmentioning
confidence: 99%
“…The development of HPV-16 associated lesions, the most common high risk HPV subtype and that has early progression [ 302 ], is connected with the ineffective immune response against HPV-16 E6 and E7 [ 310 ]. The immune status also appears to influence the prevalence of HPV-18, which is between 15% and 18% in immunocompetent women and approximately 80% in immunocompromised women [ 300 ].…”
Section: Immunity Of Female Genital Mucosa Hiv/aids and Stdsmentioning
confidence: 99%